Towards a Competence-Based View on Models and Modeling in Science Education - Upmeier zu Belzen, Annette; Krüger, Dirk; van Driel, Jan (Models and Modeling in Science Education, 2019)
XI, 321 p. 42 illus., 10 illus. in color.